Prediction of delayed graft function and long-term graft survival by serum and urinary neutrophil gelatinase-associated lipocalin during the early postoperative phase after kidney transplantation. - Herbert Thomas Maier; Muhammad Imtiaz Ashraf; Christian Denecke; Sascha Weiss; Florian Augustin; Franka Messner; Natalie Vallant; Matthias Böcklein; Christian Margreiter; Georg Göbel; Johann Pratschke; Dietmar Öfner-Velano; et al. (PLoS ONE, 2018)
Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as an early marker protein for kidney dysfunction in various clinical settings. In this prospective study we evaluated serial changes of serum and urinary NGAL within the first 7 days after kidney transplantation in 170 consecutive recipients. The main focus of this study was to assess the performance of serum and urinary NGAL in the prediction of delayed graft function (DGF) and two-year graft and patient survival. Serum and urine samples of 170 patients undergoing primary kidney transplantation from October 2010 to December 2012 were prospectively collected from day 0 to 7. NGAL was analyzed by ELISA. Multivariate regression models, receiver-operating characteristics (ROC), and areas under ROC curves (AUC) were used to identify predictors of DGF. DGF occurred in 52 patients (30.6%). Serum (AUC = 0.869) and urinary NGAL (AUC = 0.872) on postoperative day (POD) 2 could accurately predict DGF compared to serum creatinine (AUC = 0.619). Multivariate analyses revealed donor age, serum and urinary NGAL significantly associated with DGF (p<0.001). Recipient age was the only significant factor in a cox regression model influencing two-year graft and patient survival. In conclusion, serum and urinary NGAL are early predictors of DGF after kidney transplantation.